Analysis of the effect of platelet-derived growth factor combined with T cells in the diagnosis of hepatocellular carcinoma and poor prognosis - Wu, Fei; Chen, Guo; Wang, Zuxin; Niu, Youquan; Zhang, Wenqing; Jiang, Hua (Journal of Medical Biochemistry, 2025)
Objective: The aim of this study is to investigate the diagnostic and prognostic value of combined detection of serum platelet-derived growth factor (PDGF) and Treg/Th17 in hepatocellular carcinoma (HCC). Methods: We included 204 HCC patients managed with drug eluting beads-transcatheter arterial chemoembolization (D-TACE) and 100 healthy controls. Serum PDGF concentrations were measured via enzyme-linked immunosorbent assay (ELISA), while flow cytometry quantified Treg and Th17 cell proportions. The predictive performance of PDGF, Th17/Treg, and their combination for HCC diagnosis, therapeutic response, and 1-year overall survival (OS) was evaluated using receiver operating characteristic (ROC) analysis, Kaplan-Meier survival curves, and multivariate regression models. Results: HCC cases exhibited notable elevations in serum PDGF concentrations and Th17/Treg than healthy controls, with tumor tissue PDGF expression significantly correlating with serum levels (P<0.05). In addition, we found a positive correlation between PDGF, Th17/Treg and tumor markers in HCC patients (P<0.05). PDGF + Th17/Treg detection yielded an area under the curve (AUC) of 0.835 (68.14% sensitivity, 82.00% specificity), surpassing individual markers. For predicting D-TACE non-response (progressive disease, PD), the combined detection showed 71.70% sensitivity and 84.11% specificity. The 1-year OS rates of the high PDGF group and the high Th17/Treg group were 75.19% (97/129) and 61.22% (30/49), respectively, while the 1-year OS rates of the low PDGF group and the low Th17/Treg group were 92.00% (69/75) and 87.74% (136/155), respectively (P<0.05). The AUC of the combined model for predicting death was 0.705. Conclusion: PDGF combined with Th17/Treg showed excellent diagnostic value for the occurrence and poor prognosis of HCC.